Visual Repetition and Quantitative Descriptive Analysis of Visual Discourse in Environmental Activism Posters: The Work of Nobodycorp.org in the Bali Rejects Benoa Bay Reclamation - I Gusti Ngurah Tri Marutama; Bambang Sunarto; Bambang Sugiharto (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This article examines twelve environmental activism posters from the